Suggested format for university assessment in undergraduate competency based curriculum in otorhinolaryngology - Khilnani, Ajeet Kumar; Khilnani, Gurudas; Thaddanee, Rekha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The competency based medical education emphasizes role of formative and summative assessments in academic progression of learners. The university examination represents summative assessment in which distribution of marks becomes important for overall evaluation of students’ performance in examinations. The competency based curriculum (CBC) began with 2019-20 batch that has already completed phase-I training and is studying in phase-II presently. The phase-III, part-1 training for this batch would begin in February 2022. The details of otorhinolaryngology (ORL) curriculum have already been published by erstwhile Medical Council of India (MCI). There shall be formative and summative assessment examinations during the 12 months period (duration of phase-III, part-1 has been reduced from 13 months to 12 months as per the advisory from National Medical Commission). The suggested break-up of the internal assessment (IA) marks in ORL is published earlier. Here, we further suggest scheme of theory paper and clinical examination, and division of university assessment (UA) marks in ORL. The CBC document has assigned total 200 marks in ORL i.e. 100 marks for theory and 100 marks for practical/clinical examination including viva. The IA marks will not contribute to the university marks, but will be displayed as a separate head in the marksheet.